A framework for automating security analysis of the internet of things. (1st April 2017) - Ge, Mengmeng; Hong, Jin B.; Guttmann, Walter; Kim, Dong Seong
Abstract: The Internet of Things (IoT) is enabling innovative applications in various domains. Due to its heterogeneous and wide-scale structure, it introduces many new security issues. To address this problem, we propose a framework for modeling and assessing the security of the IoT and provide a formal definition of the framework. Generally, the framework consists of five phases: (1) data processing, (2) security model generation, (3) security visualization, (4) security analysis, and (5) model updates. Using the framework, we can find potential attack scenarios in the IoT, analyze the security of the IoT through well-defined security metrics, and assess the effectiveness of different defense strategies. The framework is evaluated via three scenarios, which are the smart home, wearable healthcare monitoring and environment monitoring scenarios. We use the analysis results to show the capabilities of the proposed framework for finding potential attack paths and mitigating the impact of attacks.